Indication to Colectomy in the Hands of the Academic Gastroenterologist Versus the Surgeon: Old Giant Combat While Modern “Precision Medicine” Is Timidly Waving Hand to Offer Possible Help - Giovanni Clemente Actis,; Rinaldo Pellicano,; Davide Giuseppe Ribaldone, (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Actis GC, Pellicano R, Ribaldone DG. Indication to colectomy in the hands of the academic gastroenterologist versus the surgeon: Old giant combat while modern “precision medicine” is timidly waving hand to offer possible help. Turk J Gastroenterol. 2023;34(4):433-434.